Low-level laser therapy (LLLT) accelerates the sternomastoid muscle regeneration process after myonecrosis due to bupivacaine - Alessi Pissulin, Cristiane Neves [UNESP]; Henrique Fernandes, Ana Angï¿½lica [UNESP]; Sanchez Orellana, Alejandro Manuel [UNESP]; Rossi e Silva, Renata Calciolari; Michelin Matheus, Selma Maria [UNESP] (Elsevier, 2017)
Background Because of its long-lasting analgesic action, bupivacaine is an anesthetic used for peripheral nerve block and relief of postoperative pain. Muscle degeneration and neurotoxicity are its main limitations. There is strong evidence that low-level laser therapy (LLLT) assists in muscle and nerve repair. The authors evaluated the effects of a Gallium Arsenide laser (GaAs), on the regeneration of muscle fibers of the sternomastoid muscle and accessory nerve after injection of bupivacaine. Methods In total, 30 Wistar adult rats were divided into 2 groups: control group (C: nï¿½=ï¿½15) and laser group (L: nï¿½=ï¿½15). The groups were subdivided by antimere, with 0.5% bupivacaine injected on the right and 0.9% sodium chloride on the left. LLLT (GaAs 904ï¿½nm, 0,05ï¿½W, 2.8ï¿½J per point) was administered for 5 consecutive days, starting 24ï¿½h after injection of the solutions. Seven days after the trial period, blood samples were collected for determination of creatine kinase (CK). The sternomastoid nerve was removed for morphological and morphometric analyses; the surface portion of the sternomastoid muscle was used for histopathological and ultrastructural analyses. Muscle CK and TNFα protein levels were measured. Results The anesthetic promoted myonecrosis and increased muscle CK without neurotoxic effects. The LLLT reduced myonecrosis, characterized by a decrease in muscle CK levels, inflammation, necrosis, and atrophy, as well as the number of central nuclei in the muscle fibers and the percentage of collagen. TNFα values remained constant. Conclusions LLLT, at the dose used, reduced fibrosis and myonecrosis in the sternomastoid muscle triggered by bupivacaine, accelerating the muscle regeneration process.
Keywords: Bupivacaine; Fibrosis; Low-level light therapy; Muscle regeneration